M221. THE EFFECT OF LIFE SKILLS TRAINING ON FUNCTIONING IN SCHIZOPHRENIA: A RANDOMIZED CONTROLLED TRIAL. (18th May 2020) - Abaoğlu, Hatice; Mutlu, Emre; Ak, Sertaç; Akı, Esra; Elif Anıl Yağcıoğlu, A
Abstract: Background: The combined use of pharmacological and non-pharmacological psychosocial interventions is seen as the most effective treatment approaches to improve the long term outcomes in schizophrenia. The psychosocial interventions aim to improve social skills, self-efficacy, being independent in activities of daily living and interpersonal communication in people diagnosed with schizophrenia. They include various approaches, such as cognitive behavioral therapy, cognitive remediation, individual, group or family therapies and life skills trainings. Life skills training approaches aim to assist individuals gain skills necessary for fulfilling their roles in the environment they live in, and consist of parts including assessment, teaching, behavioral practice, feedback, and homework, covering areas such as self-care, money management, communication and social skills, home management and community life. In this study, we planned to investigate the effects of individualized life skills training on the functionality of individuals diagnosed with schizophrenia. Methods: A total of 32 individuals diagnosed with schizophrenia were assigned randomly to the life skills training (n=15) and the control groups (n=17). The participants were assessed with the Positive and Negative Syndrome Scale (PANSS) for symptom severity, the Clinical Global Impression Scale for illness severity, improvement and response to treatment, the Katz Index of Independence in Activities of Daily Living and the Lawton – Brody Instrumental Activities of Daily Living Scale for adequacy of performance of basic activities and tasks of daily living, the Functioning Assessment Short Test and Social Functioning Scale for level of functionality before and after the scheduled interventions in both groups. The control group received a single-session awareness training to increase independence in daily living activities, and the life skills training group received individualized life skills training in 2 sessions per week for 8 weeks (i.e. 16 sessions). Results: The life skills training and control groups did not differ significantly on the bases of age, gender, working status, marital status, education (years), age at onset and duration of illness. The groups were similar in terms of pharmacological treatment choices. At the end of the research program, improvements were observed in the negative symptoms, general psychopathology, severity of illness and independence in basic and instrumental activities of daily living and functioning in the life skills training group as compared to the control group. Discussion: Our study showed that the training planned to improve life skills in individuals with chronic schizophrenia during the transition period from the hospital to the community environment, decreased negative symptoms and had a positive effect on general psychopathology and illness severity. Individual based life skills training, which focused less on social learning principles and aimed to increase independence in daily life, demonstrated positive effects on patient functionality. On the basis of the obtained results, it can be suggested that individualized life skills training may be an effective therapeutic method for the rehabilitation of individuals diagnosed with schizophrenia. The effect of individualized life skills training should be investigated and supported by long-term follow-up studies.